Ivan Franko about Ethnic Education of Ukrainian Youth - Budnyk, Olena (Pedagogical Discourse, 2012)
The article gives characteristics of main ideas of concept of ethnic education of Ukrainian youth by Ivan Franko during the processes of globalization. Much attention is given to formation of national consciousness of personality, readiness of young people for the participation in state creation processes on the basis of humanism and freedom.